PENGARUH STRATEGI GAMIFIKASI DENGAN PENDEKATAN PEMBELAJARAN MENDALAM TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SD KELAS V KECAMATAN WARU - Kartika Dwi Astuti; Muhamad Sofian Hadi; Viarti Eminita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of gamification strategies with an immersive learning approach on the critical thinking skills of fifth-grade elementary school students in Waru District. The background of this study is the low critical thinking skills of students caused by teacher-centered learning, the lack of innovative strategies, and the suboptimal use of immersive learning approaches. The gamification strategy was chosen because it can increase motivation and learning engagement through game elements, while the immersive learning approach encourages conceptual understanding, reflection, and higher-order reasoning. This study used a quasi-experimental method with a pretest–posttest design in several elementary schools in Waru District. The research sample was fifth-grade students determined through relevant sampling techniques. Data collection was carried out through critical thinking ability tests, observation, and documentation. The test instruments were designed based on critical thinking indicators including interpretation, analysis, evaluation, and inference. Validity and reliability tests of the instruments were conducted before use. Data were analyzed using inferential statistical tests, including difference tests and repeated measures ANOVA to examine the effect of treatment and differences between schools. The expected results of this study are an increase in critical thinking skills in students who are taught using immersive learning-based gamification strategies compared to conventional learning, as well as differences in the level of improvement between schools. This research is expected to provide theoretical and practical contributions to the development of innovative learning strategies in elementary schools to strengthen students' critical thinking skills.